In-silico analysis of peptidoglycan hydrolases from Serratia marcescens and other Serratia species. (23rd June 2020) - Rathee, Aditi; Gupta, Kanika; Kumari, Seema; Chhibber, Sanjay; Kumar, Ashok
Bacteria possess a protective extracytoplasmic glycopeptide polymer, i.e., peptidoglycan. In case of Gram-positive bacteria, it acts as scaffolds to many virulence factors whereas in Gram-negative bacteria, it serves as an anchor to outer membrane. Many antibiotics act on bacteria by inhibiting the activity of enzymes involved in the synthesis of peptidoglycan. However during the years, overexposure of antibiotics has led to modification of peptidoglycan chain by bacteria viz. N-deacetylation, N-glycolylation and O-acetylation, etc. Peptidoglycan hydrolases are known to play an important role in the suppression of bacterial infections as a component of the innate immune system as well as disintegrating peptidoglycan which is an important factor in the pathogenesis of various organisms. Present study explicates computational analysis of a peptidoglycan hydrolase enzyme from a total of 41 fully sequenced genomes of Serratia marcescens and other Serratia species. Seventy-five unique motifs were identified among the protein sequences of peptidoglycan hydrolase.